Stellar differential rotation in theory and observation. Issue 1 (6th February 2013) - Czesla, S.; Arlt, R.; Bonanno, A.; Strassmeier, K.G.; Huber, K.F.
Abstract Stellar differential rotation is intimately related to the stellar magnetic dynamo and, thus, to stellar activity. In recent years, significant progress in the measurement of differential rotation on the basis of Doppler imaging techniques and the availability of space‐based long‐term photometry has been achieved. Similarly, simulations incorporate ever more details of the complexity of convective zones. While some aspects of solar and stellar differential rotation can be explained now, several important questions remain open or controversial. In this splinter session, we discussed the latest observational and theoretical progress in the field of differential rotation. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)